Influencing Factors’ Analysis of Disturbance Degree of Key Stratum Based on the Response Surface Method - Yang Li; Nan Wang; Yuqi Ren; Xiangji Ou; Yikun Liu; Junbo Luo; Canqi Mei (Advances in Civil Engineering)
The key stratum controls the activities of the overlying strata or the whole strata up to the surface, which is one of the important research objects in the coal seam mining. Based on the analysis of several geological factors affecting on the key stratum, the definition of “disturbance degree of key stratum” (KSDD) was proposed. And, the KSDD is quantified by the value among 0 to 10. Through the response surface method, experiments of three factors (mining height, buried depth, and interlayer spacing) with three different lithology types (soft, medium, and hard) between key stratum and coal seam are signed. And, the KSDD of each scheme is calculated by the developed calculation system. The response surface regression models of KSDD with three lithology types are established. And, the single influence and interactive influences of the three factors on the KSDD with different lithology types are studied. The results show that the following. (1) Mining height and buried depth are positively correlated with the value of KSDD, and the interlayer spacing is negatively correlated with KSDD. However, when the value of interlayer spacing exceeds 30 m, the change of the KSDD tends to be gentle. (2) The value of KSDD is not only affected by a single factor but also affected by the interaction of various factors. With the increase of burial depth, the decrease of interlayer spacing and the impact of mining height on key stratum are more severe. (3) The influence order of each factor on KSDD is as follows: the interlayer spacing > mining height > buried depth. (4) Although the three factors interact with each other, the three factors decrease with the increase of the lithology proportional coefficient. According to the above research results, based on the calculation results of KSDD on five mines, the variation laws of KSDD with actual situation are analysed. And, the calculation results further verify the above experimental rules, which provide a certain reference and theoretical basis for the design of backfilling parameters and the management of the roof.